Building Customer Loyalty in Digital Commerce: The Roles of Electronic Trust, E-CRM, and Customer Satisfaction - Gregoria Cici Anjarwati; Ramadania; Bintoro Bagus Purmono; Juniwati; Harry Setiawan (Al-Qalam Institue, 2026)
This study aims to analyze the effects of electronic trust and Electronic Customer Relationship Management (E-CRM) on customer loyalty through customer satisfaction among Generation Z Shopee users. This study employed a quantitative approach with a causal associative survey design. Data were collected through an online questionnaire using a five-point Likert scale from 217 Generation Z respondents who had made purchases on Shopee within the previous six months. The respondents were selected using non-probability sampling with a purposive sampling technique. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results indicate that electronic trust and E-CRM have positive and significant effects on customer satisfaction and customer loyalty. Customer satisfaction also has a positive and significant effect on customer loyalty. Furthermore, customer satisfaction significantly mediates the effects of electronic trust and E-CRM on customer loyalty. These findings imply that strengthening transaction security, improving digital service quality, and implementing effective customer relationship management can enhance customer satisfaction and loyalty among Generation Z users. The findings provide practical insights for e-commerce platforms in developing strategies to build trust, strengthen customer relationships, and foster long-term customer loyalty.